EFFECT OF DIFFERENT LEVELS OF PHOSPHORUS INPUT ON PHYTOPLANKTON PRODUCTIVITY IN LIMED ACID SULFATE SOILS FISHPOND - Abdul Karim Gaffar (Research Center for Fisheries, 1997)
One of problems of building lishponds in acid sulfate soil areas is their poor responseto fertilization.